Polyethylene microfiber Janus composite membrane as well as preparation method and application thereof
Polyethylene microfiber membranes were prepared by instantaneous pressure relief method and single-sided modification of dopamine and hydrophilic polymers were performed to form an efficient Janus composite membrane, which solved the problems of low oil-water separation efficiency and complex preparation in the prior art, and achieved high efficiency The goal of oil-water separation and simplification of process.
Patent Information
- Application Number
- CN202411259479.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing Janus composite membranes have low oil-water separation efficiency, complicated preparation process and high cost.
The polyethylene microfiber membrane was prepared by instantaneous pressure relief method, and a composite layer was formed by reacting single-side impregnation of dopamine and hydrophilic polymer to form a composite layer to form a Janus composite membrane with hydrophobic and hydrophilic properties, thereby improving the oil-water separation efficiency.
The efficient oil-water separation efficiency of polyethylene microfiber Janus composite film is achieved, up to 99.95%, and the preparation process is simplified, cost is reduced, and it is suitable for large-scale production.
Smart Images

Figure CN119113816A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of novel oil-water separation membranes, and in particular relates to a polyethylene microfiber Janus composite membrane and a preparation method and application thereof. Background Art
[0002] Janus membrane generally refers to a membrane material with asymmetric morphology or chemical composition on both sides of the membrane, that is, the morphology or chemical composition on both sides of the membrane is anisotropic. This asymmetric anisotropy gives Janus membranes some excellent physical, chemical, biological and other properties that are superior to traditional homogeneous membranes, becoming a new direction in the field of membrane materials and membrane research. Usually, chemical asymmetric modification methods are used to post-modify both sides of the membrane to achieve the construction of Janus membranes. However, there are still deficiencies in process flow, cost and separation efficiency, so there is an urgent need to develop Janus membranes with low cost and high separation efficiency.
[0003] The prior art with publication number CN115418795A discloses a Janus-type micro-nano composite fiber membrane with one side super-hydrophobic and one side super-hydrophilic and a preparation method thereof, wherein a polytetrafluoroethylene / polyvinyl alcohol / titanium dioxide (PTFE / PVA / TiO 2 ) composite fiber membrane, and high temperature sintering to prepare hydrophobic micro-nano PTFE / TiO 2 The fiber membrane was then modified on one side in PDA buffer to prepare a single-sided super-hydrophobic and single-sided super-hydrophilic Janus-type micro-nano composite fiber membrane.
[0004] However, the Janus composite membrane mentioned above has the following problems in practical application: first, the oil-water separation efficiency is low, which is 98.7% at most, limiting its application scope; second, the preparation process is complicated, the conditions are harsh, the cost is high, and it is not conducive to industrial production. Summary of the invention
[0005] The invention discloses a polyethylene microfiber Janus composite membrane and a preparation method and application thereof, aiming to solve the technical problems of the existing Janus composite membrane, namely, complicated preparation process, harsh conditions and low oil-water separation efficiency.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] The first aspect of the present invention provides a polyethylene microfiber Janus composite membrane, comprising a polyethylene microfiber membrane and a composite layer formed by the reaction of polydopamine and a hydrophilic polymer covering one side of the polyethylene microfiber membrane;
[0008] The polyethylene microfiber membrane is prepared by an instantaneous pressure release method, and has a fiber diameter of 500nm-20μm and a pore size of 1-50μm;
[0009] The hydrophilic polymer has a disulfide bond or a trisulfide bond group at the end;
[0010] The polymer is one of poly-[2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide, polyethylene glycol, poly(N,N-dimethylacrylamide), polyvinyl pyrrolidone and polyacrylic acid.
[0011] In combination with the first aspect, preferably, the disulfide bond group is one of a dithioester group, a xanthate group, and a dithiocarbamate group;
[0012] And / or, the trisulfide bond group is a trithiocarbonate group.
[0013] The second aspect of the present invention provides a method for preparing the polyethylene microfiber Janus composite membrane according to the first aspect, the method comprising:
[0014] The polyethylene microfiber membrane is immersed on one side in a buffer solution containing dopamine to react, thereby obtaining a polydopamine@polyethylene microfiber membrane;
[0015] The polydopamine@polyethylene microfiber membrane containing polydopamine is immersed in a mixed solution containing sodium borohydride and a hydrophilic polymer for reaction to obtain a polyethylene microfiber Janus composite membrane.
[0016] In combination with the second aspect, preferably, the buffer solution comprises tris(hydroxymethyl)aminomethane buffer with a concentration of 10-50 mM and a pH of 8.0-9.0.
[0017] In combination with the second aspect, preferably, the concentration of the buffer solution containing dopamine is 2-4 mg / mL.
[0018] In combination with the second aspect, preferably, the polyethylene microfiber membrane is immersed on one side in the buffer solution containing dopamine for a reaction time of 12-36 hours.
[0019] In conjunction with the second aspect, preferably, the concentration of the hydrophilic polymer is 2-4 mg / mL.
[0020] In combination with the second aspect, preferably, the molar ratio of the hydrophilic polymer to sodium borohydride is 1:1-5.
[0021] In combination with the second aspect, preferably, the polydopamine-containing surface of the polydopamine@polyethylene microfiber membrane is immersed in a mixed solution containing sodium borohydride and a hydrophilic polymer for a reaction time of 12-36 hours.
[0022] The third aspect of the present invention provides the use of the polyethylene microfiber Janus composite membrane described in the second aspect in oil-water separation.
[0023] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present invention include at least:
[0024] The polyethylene microfiber Janus composite membrane provided by the present invention uses polydopamine and a hydrophilic polymer to modify a polyethylene microfiber membrane with a diameter of 500nm-20μm and a pore size of 1-50μm on one side by a simple floating method. The polyethylene microfiber has a full carbon chain and regular molecular arrangement structure, and has a high degree of crystallinity and molecular weight, thereby reducing the surface free energy of the fiber, making it difficult for water molecules to adhere, increasing the surface contact angle, and giving one side of the Janus composite membrane excellent hydrophobic properties. At the same time, the polymer composite layer after the polydopamine hydrophilic coating self-assembled by dopamine on the surface of the polyethylene microfiber membrane and the hydrophilic polymer containing disulfide bonds or trisulfide bond groups at the end reacts can improve the affinity and surface energy, and give the other side of the Janus composite membrane excellent hydrophilic properties; due to the different wettability on both sides of the membrane, under the impetus of the surface chemical potential, the oil-water mixture undergoes anisotropic transport between the porous cross-section layers of the membrane material, thereby achieving efficient oil-water separation.
[0025] In addition, the present invention adopts a single-sided impregnation preparation method, so that the prepared polyethylene microfiber Janus composite membrane has good hydrophilic and hydrophobic double-sided anisotropy, and the oil-water separation efficiency can reach up to 99.95%. The preparation process is simple, the operation is easy, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 is a SEM image of a polyethylene microfiber membrane according to an embodiment of the present invention;
[0028] Figure 2 is a mechanical properties diagram of a polyethylene microfiber membrane according to an embodiment of the present invention;
[0029] Wherein: (a) is the tensile strength and elongation at break of polyethylene microfiber membrane and α1-polyethylene microfiber Janus composite membrane; (b) is the stress-strain diagram of polyethylene microfiber membrane and α1-polyethylene microfiber Janus composite membrane;
[0030] Figure 3 is a SEM image of the α1-polyethylene microfiber Janus composite membrane prepared in an embodiment of the present invention;
[0031] Figure 4 is a comparison diagram of the contact angles of the α1-polyethylene microfiber Janus composite membrane prepared in the embodiment of the present invention in air;
[0032] Figure 5 This is a comparison chart of contact angle tests of the α1-polyethylene microfiber Janus composite membrane prepared in an embodiment of the present invention in air and under liquid;
[0033] Figure 6 This is an experimental diagram of oil-water separation of the α1-polyethylene microfiber Janus composite membrane prepared in an embodiment of the present invention;
[0034] Figure 7 It is a diagram of oil-water separation efficiency and flux of the α1-polyethylene microfiber Janus composite membrane prepared in the embodiment of the present invention. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0037] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0038] Those skilled in the art should understand that, in the description of the embodiments of the present invention, the order of serial numbers does not mean the order of execution, some or all of the steps may be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0039] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "an" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0040] It should be noted that all raw materials and / or reagents in the examples of the present invention are purchased on the market or prepared according to conventional methods known to those skilled in the art. For example, polyethylene microfiber membrane, dopamine, poly-[2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide (PDMAPS) and tris(hydroxymethyl)aminomethane buffer solution are all purchased on the market.
[0041] In a first aspect, an embodiment of the present invention provides a polyethylene microfiber Janus composite membrane, comprising a polyethylene microfiber membrane and a composite layer formed by the reaction of polydopamine and a hydrophilic polymer covering one side of the polyethylene microfiber membrane;
[0042] The polyethylene microfiber membrane is prepared by an instantaneous pressure release method, and has a fiber diameter of 500nm-20μm and a pore size of 1-50μm;
[0043] The hydrophilic polymer has a disulfide bond or a trisulfide bond group at the end;
[0044] The polymer is one of poly-[2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide, polyethylene glycol, poly(N,N-dimethylacrylamide), polyvinyl pyrrolidone and polyacrylic acid.
[0045] Among them, the polyethylene microfiber has a full carbon chain and regular molecular arrangement structure, and has a high degree of crystallinity and molecular weight, which reduces the surface free energy of the fiber, making it difficult for water molecules to adhere, increasing the surface contact angle, and giving the Janus composite membrane one side excellent hydrophobic properties. At the same time, the polymer composite layer formed by the reaction of the polydopamine hydrophilic coating self-assembled by dopamine on the surface of the polyethylene microfiber membrane and the hydrophilic polymer containing disulfide bonds or trisulfide bonds at the end can improve the affinity and surface energy, giving the other side of the Janus composite membrane excellent hydrophilic properties; due to the different wettability on both sides of the membrane, driven by the surface chemical potential, the oil-water mixture undergoes anisotropic transport between the porous cross-section layers of the membrane material, thereby achieving efficient oil-water separation.
[0046] In the embodiment of the present invention, the disulfide bond group is preferably one of a dithioester group, a xanthate group, and a dithiocarbamate group, and the trisulfide bond group is preferably a trithiocarbonate group. The hydrophilic polymer used in the present invention is a polymer containing a disulfide bond or a trisulfide bond, and these groups can be reduced to sulfhydryl groups by sodium borohydride, and the sulfhydryl groups react with the catechol groups on dopamine, thereby grafting the hydrophilic polymer on the membrane surface.
[0047] In a second aspect, an embodiment of the present invention further provides a method for preparing the polyethylene microfiber Janus composite membrane according to the first aspect, the method comprising:
[0048] The polyethylene microfiber membrane is immersed on one side in a buffer solution containing dopamine to react, thereby obtaining a polydopamine@polyethylene microfiber membrane;
[0049] The polydopamine@polyethylene microfiber membrane containing polydopamine is immersed in a mixed solution containing sodium borohydride and a hydrophilic polymer for reaction to obtain a polyethylene microfiber Janus composite membrane.
[0050] It should be noted that the hydrophilic polymer is synthesized by a reversible addition-fragmentation chain transfer radical polymerization method, and has a dithioester group, a xanthate group, a dithiocarbamate group or a trithiocarbonate group at the end. The hydrophilic polymer includes one of poly-[2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide, polyethylene glycol, poly(N,N-dimethylacrylamide), polyvinyl pyrrolidone, and polyacrylic acid, and this type of compound has excellent hydrophilic properties.
[0051] In the embodiment of the present invention, the buffer solution is preferably a tris(hydroxymethyl)aminomethane buffer solution, the buffer solution concentration is preferably 10-50mM, and the pH is preferably 8.0-9.0. Tris(hydroxymethyl)aminomethane buffer solution (Tris buffer solution) has good buffering capacity within the physiological range of pH 8.0-9.0 and a concentration within the range of 10-50mM, can effectively stabilize the pH value of the solution, and can effectively resist the influence of external acid-base changes on the pH value of the solution.
[0052] In an embodiment of the present invention, the concentration of the buffer solution in which dopamine is dissolved is preferably 2-4 mg / mL. Wherein, when the concentration of the mixed solution is not within the range of 2-4 mg / mL, problems such as poor coating uniformity, poor coating stability, and low adhesion may result, affecting the stability of the super-affinity surface under the preparation liquid. Therefore, the concentration of the buffer solution in which dopamine is dissolved is preferably 2-4 mg / mL.
[0053] In an embodiment of the present invention, the polyethylene microfiber membrane is immersed in the buffer solution dissolved with dopamine on one side for a reaction time of preferably 12-36 hours. Among them, when the hydrophobic polyethylene microfiber membrane is immersed in the mixed solution on one side for a reaction time of less than 12 hours, the polydopamine layer generated on the surface of the substrate is not completely reacted, the bonding force is insufficient, and it is easy to fall off; when the reaction time is greater than 36 hours, the reaction is complete, and too long a time leads to an increase in energy consumption. Therefore, the polyethylene microfiber membrane is immersed in the buffer solution dissolved with dopamine on one side for a reaction time of preferably 12-36 hours.
[0054] In the embodiment of the present invention, the concentration of the hydrophilic polymer is preferably 2-4 mg / mL. The hydrophilic polymer is grafted onto the surface of the polyethylene microfiber membrane to give the Janus composite membrane excellent hydrophilicity and stability.
[0055] In an embodiment of the present invention, the molar ratio of the hydrophilic polymer to sodium borohydride is preferably 1: 1-5. The hydrophilic polymer is reduced by controlling the molar ratio of the hydrophilic polymer to sodium borohydride, using sodium borohydride as a reducing agent, and then reacting with polydopamine to compound the hydrophilic polymer onto the fiber surface, thereby improving the stability of the Janus composite membrane.
[0056] In the embodiment of the present invention, the reaction time of immersing the polydopamine surface of the polydopamine@polyethylene microfiber membrane in a mixed solution containing sodium borohydride and a hydrophilic polymer is preferably 12-36 hours. By controlling the reaction time, the hydrophilic polymer can be composited on one side of the polyethylene microfiber membrane, and the Janus composite membrane has good hydrophilic and hydrophobic properties on both sides.
[0057] It should be noted that the preparation method provided by the present invention uses a single-sided impregnation process to composite the polymer layer after the reaction of polydopamine and a hydrophilic polymer on one side of a polyethylene microfiber membrane. The polydopamine layer has super strong adhesion properties and can greatly improve the binding force with the polyethylene microfiber membrane. The catechol group of dopamine reacts with the thiol group of the hydrophilic polymer, thereby grafting the hydrophilic polymer on the polyethylene microfiber membrane, giving one side of the membrane excellent hydrophilicity and the other side excellent hydrophobicity, so that the Janus membrane exhibits good integrity. The prepared polyethylene microfiber Janus composite membrane has good anisotropy on both sides, and the oil-water separation efficiency can reach up to 99.95%. In addition, the preparation process is simple, the operation is easy, and it is suitable for large-scale production.
[0058] The reaction mechanism is shown in formula (1):
[0059]
[0060] In a third aspect, the embodiments of the present invention also provide the application of the polyethylene microfiber Janus composite membrane described above in oil-water separation. Among them, the polyethylene microfiber Janus composite membrane described above has a simple preparation process, good hydrophilic and hydrophobic double-sided anisotropy, and excellent oil-water separation efficiency. Therefore, when the polyethylene microfiber Janus composite membrane prepared by the present invention is used for oil-water separation, it has a high oil-water separation efficiency.
[0061] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0062] Example 1
[0063] This embodiment provides a method for preparing an α1-polyethylene microfiber Janus composite membrane, which specifically includes:
[0064] S101: weigh 200 mg of dopamine hydrochloride, dissolve it in 100 mL of a prepared tris(hydroxymethyl)aminomethane buffer solution with a pH value of 8.5, and stir to obtain a 2 mg / mL polydopamine solution; float a single side of a polyethylene microfiber membrane in the prepared polydopamine solution to react for 24 hours, take it out and rinse it thoroughly with deionized water and ethanol, and dry it to obtain an α1-polydopamine@polyethylene composite membrane;
[0065] S102: Weigh 200 mg of PDMAPS containing dithiobenzoate groups, dissolve it in 100 mL of the prepared tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.5, add 20 mg of sodium borohydride, and stir for a period of time to obtain a 2 mg / mL mixed solution; float the polydopamine@polyethylene composite membrane containing the polydopamine side in the prepared PDMAPS and sodium borohydride mixed solution for reaction for 24 hours, take out and rinse thoroughly with deionized water and ethanol, and dry to obtain an α1-polyethylene microfiber Janus composite membrane.
[0066] Example 2
[0067] This embodiment provides a method for preparing an α2-polyethylene microfiber Janus composite membrane, which specifically includes:
[0068] S201: Weigh 400 mg of dopamine hydrochloride, dissolve it in 100 mL of a prepared pH=8.0 tris(hydroxymethyl)aminomethane buffer solution, and stir to obtain a 4 mg / mL polydopamine solution; float a single side of a polyethylene microfiber membrane in the prepared polydopamine solution to react for 12 hours, take it out and rinse it thoroughly with deionized water and ethanol, and dry it to obtain an α2-polydopamine@polyethylene composite membrane;
[0069] S202: Weigh 200 mg of a polymer containing trithiocarbonate groups, PDMAPS, and dissolve it in 100 mL of a prepared pH = 8.5 tris(hydroxymethyl)aminomethane buffer solution, and add 6.67 mg of sodium borohydride. After stirring for a period of time, a 2 mg / mL mixed solution is obtained; float one side of the polydopamine@polyethylene composite membrane in the prepared PDMAPS and sodium borohydride mixed solution and react for 12 hours. Take it out, rinse it thoroughly with deionized water and ethanol, and dry it to obtain an α2-polyethylene microfiber Janus composite membrane.
[0070] Example 3
[0071] This embodiment provides a method for preparing an α3-polyethylene microfiber Janus composite membrane, which specifically includes:
[0072] S301: weigh 300 mg of dopamine hydrochloride, dissolve it in 100 mL of a prepared tris(hydroxymethyl)aminomethane buffer solution with a pH value of 8.5, and stir to obtain a 3 mg / mL polydopamine solution; float a single side of a polyethylene microfiber membrane in the prepared polydopamine solution to react for 36 hours, take it out and rinse it thoroughly with deionized water and ethanol, and dry it to obtain an α3-polydopamine@polyethylene composite membrane;
[0073] S302: Weigh 200 mg of PDMAPS containing a trithiocarbonate group, dissolve it in 100 mL of a prepared tris(hydroxymethyl)aminomethane buffer solution at pH = 8.5, add 20 mg of sodium borohydride, and stir for a period of time to obtain a 2 mg / mL mixed solution; float one side of the polydopamine@polyethylene composite membrane in the prepared mixed solution of PDMAPS and sodium borohydride to react for 36 hours, take it out, rinse it thoroughly with deionized water and ethanol, and dry it to obtain an α3-polyethylene microfiber Janus composite membrane.
[0074] Example 4
[0075] This embodiment provides a method for preparing an α4-polyethylene microfiber Janus composite membrane, which specifically includes:
[0076] S401: Weigh 200 mg of dopamine hydrochloride, dissolve it in 100 mL of a prepared tris(hydroxymethyl)aminomethane buffer solution with a pH value of 9.0, and stir to obtain a 2 mg / mL polydopamine solution; float a single side of a polyethylene microfiber membrane in the prepared polydopamine solution to react for 12 hours, take it out and rinse it thoroughly with deionized water and ethanol, and dry it to obtain an α4-polydopamine@polyethylene composite membrane;
[0077] S402: Weigh 200 mg of PDMAPS containing dithiobenzoate, dissolve it in 100 mL of prepared tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.5, add 33.33 mg of sodium borohydride, and stir for a period of time to obtain a 2 mg / mL mixed solution; float one side of the polydopamine@polyethylene composite membrane in the prepared mixed solution of PDMAPS and sodium borohydride to react for 24 hours, take out and rinse thoroughly with deionized water and ethanol, and dry to obtain an α4-polyethylene microfiber Janus composite membrane.
[0078] Example 5
[0079] This embodiment provides a method for preparing an α5-polyethylene microfiber Janus composite membrane, which specifically includes:
[0080] S501: Weigh 200 mg of dopamine hydrochloride, dissolve it in 100 mL of a prepared tris(hydroxymethyl)aminomethane buffer solution with a pH value of 8.5, and stir to obtain a 2 mg / mL polydopamine solution; float a single side of a polyethylene microfiber membrane in the prepared polydopamine solution to react for 24 hours, take it out and rinse it thoroughly with deionized water and ethanol, and dry it to obtain an α5-polydopamine@polyethylene composite membrane;
[0081] S502: Weigh 200 mg of polyethylene glycol containing dithiobenzoate, dissolve it in 100 mL of prepared tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.5, add 20 mg of sodium borohydride, and stir for a period of time to obtain a 2 mg / mL mixed solution; float one side of the polydopamine@polyethylene composite membrane in the prepared polyethylene glycol and sodium borohydride mixed solution to react for 24 hours, take out and rinse thoroughly with deionized water and ethanol, and dry to obtain an α5-polyethylene microfiber Janus composite membrane.
[0082] Comparative Example 1 of the present invention uses the provided polyethylene microfiber membrane.
[0083] The β2-polydopamine@polyethylene composite membrane provided in Comparative Example 2 of the present invention has the same preparation process as that in Example 1, and only one side of the polyethylene microfiber membrane is subjected to a polydopamine modification treatment.
[0084] In order to verify the morphology, structure and mechanical properties of the polyethylene microfiber membrane and α1-polyethylene microfiber Janus composite membrane prepared in the examples and comparative examples of the present invention, the α1-polyethylene microfiber Janus composite membrane prepared in the examples was characterized. The results are as follows: Figure 1-Figure 3 As shown. Among them, Figure 1 This is the SEM image of the polyethylene microfiber membrane; Figure 2 is the mechanical properties diagram of polyethylene microfiber membrane, where: Figure 2a is the tensile strength and elongation at break of polyethylene microfiber membrane and α1-polyethylene microfiber Janus composite membrane; Figure 2 b is the stress-strain diagram of polyethylene microfiber membrane and α1-polyethylene microfiber Janus composite membrane; Figure 3 This is the SEM image of α1-polyethylene microfiber Janus composite membrane.
[0085] according to Figure 1 It can be seen that the polyethylene microfiber membrane presents a fibrous structure, the fiber surface is relatively smooth, and the average pore size is 4.2 μm.
[0086] according to Figure 2 visible, Figure 2 The polyethylene microfiber membrane in (a) has excellent breaking strength and breaking elongation, with a breaking strength of 28.01Mpa and a breaking elongation of 27.63%; the breaking strength of the α1-polyethylene microfiber Janus composite membrane is 27.00Mpa and the breaking elongation is 37.04%. Figure 2 From (a) and (b), we can see that the α1-polyethylene microfiber Janus composite film also has excellent mechanical properties.
[0087] according to Figure 3 It can be seen that after single-sided modification by polydopamine and PDMAPS, it can be obviously found that the surface of the prepared polyethylene microfiber membrane becomes rough, indicating that polydopamine and PDMAPS have been composited on the surface of the polyethylene microfiber membrane, and the average pore size is 0.21 μm.
[0088] In order to verify the oil-water separation performance of the Janus membrane prepared in the embodiment of the present invention, the α1-polyethylene microfiber Janus composite membrane prepared in the embodiment was tested for oil-water separation. The results are as follows: Figure 4-Figure 7 As shown. Among them, Figure 4 is a comparison diagram of the contact angles of the α1-polyethylene microfiber Janus composite membrane prepared in the embodiment of the present invention in air; Figure 5 It is a contact angle experimental diagram of the α1-polyethylene microfiber Janus composite film prepared in the embodiment of the present invention in air and under liquid; Figure 6 This is an experimental diagram of oil-water separation of the α1-polyethylene microfiber Janus composite membrane prepared in an embodiment of the present invention; Figure 7 This is a diagram of the oil-water flux of the α1-polyethylene microfiber Janus composite membrane prepared in an embodiment of the present invention.
[0089] Oil-water separation experiment: The polyethylene microfiber Janus composite membrane prepared in the above embodiment is used to perform oil-water separation application test on the oil-water mixed solution of dodecane and deionized water and dichloromethane and deionized water (the volume ratio of water / dodecane mixed solution is 1:1, and the volume ratio of water / dichloromethane mixed solution is 1:1). The oil-water mixed solution is separated using a filtering device. When the hydrophobic surface (front side) faces upward, water is intercepted and dichloromethane filtrate is obtained, and the separation efficiency reaches 99.95%; when the hydrophilic surface faces upward, dodecane is intercepted and water filtrate is obtained, and the separation efficiency is as high as 99.52%. The separation efficiency of the polyethylene microfiber Janus composite membrane prepared by this preparation method is above 99%, among which the oil-water separation rate of Example 1 is the highest, and the separation efficiency is as high as 99.95%, indicating that it has a good oil-water separation effect.
[0090] Contact angle test: drop a drop of liquid on the horizontal surface in the air and under the liquid, test the angle between the two tangent lines of the gas-liquid interface and the solid-liquid interface, and characterize the wettability of the liquid to the solid. First, adjust the position of the capillary needle and the platform, so that the capillary needle appears at 1 / 3 of the lens, fix the 2cm*2cm coating surface on the glass slide facing up, use the capillary needle to drop 3.0μL of water on the coating surface, wait for the contact angle to stabilize, use the camera in the instrument to shoot the drop contact surface, and then measure the contact angle. Take the average of three or more times as the water contact angle value of the coating surface.
[0091] according to Figure 4 It can be seen that the pure polyethylene microfiber membrane is hydrophobic. After being modified with polydopamine and PDMAPS on one side, the surface contains abundant anions -SO 3 - and cation N + (CH 3 ) 2 The contact angle of water is significantly reduced to 9.2°, which is hydrophilic, while the polyethylene microfiber membrane on the other side is still hydrophobic, and the contact angle does not change much after modification.
[0092] according to Figure 5It can be seen that the contact angle of water on the front side of the polyethylene microfiber membrane is 110.4°, the contact angle of oil is 0°, the contact angle of oil under water is 0°, and the contact angle of water under oil is 125.4°; the contact angle of water on the front side of the α1-polyethylene microfiber Janus composite membrane is 9.2°, the contact angle of oil is 0°, the contact angle of oil under water is 158.2°, and the contact angle of water under oil is 139.1°; the contact angle of water on the back side of the polyethylene microfiber membrane is 123. The contact angle of water on the back of α1-polyethylene microfiber Janus composite membrane is 112.6°, the contact angle of oil is 0°, the contact angle of oil underwater is 0°, and the contact angle of water under oil is 141.8°; the pure polyethylene microfiber membrane is hydrophobic in water under oil. After single-sided modification, it is not only hydrophobic under oil, but also oleophobic in water.
[0093] according to Figure 6 It can be seen that the α1 polyethylene microfiber Janus composite membrane is used to separate the original solution and filtrate of the oil-water mixture, including (a) water and dichloromethane mixture and filtrate; (b) water and dodecane mixture and filtrate. After the oil-water mixture is separated by the prepared α1 polyethylene microfiber Janus composite membrane, it can be obviously found that the oil and water are efficiently separated.
[0094] according to Figure 7 It can be seen that the oil-water mixture was separated by the prepared α1 polyethylene microfiber Janus composite membrane, and the oil flux was as high as 1103 L·m -2 ·h -1 , water flux 392L·m -2 ·h -1 , while the oil flux of the original polyethylene membrane is 122 L·m -2 ·h -1 , water flux is 0L·m -2 ·h -1 The separation flux of the modified α1 polyethylene microfiber Janus composite membrane was greatly improved.
[0095] According to the present invention, by changing the soaking time, concentration and pH in Example 1 and Example 2, and by changing the soaking time and pH in Example 1 and Example 4, the prepared polyethylene microfiber Janus composite membrane has good hydrophilic and hydrophobic double-sided anisotropy and efficient oil-water separation rate. The difference between Example 1 and Comparative Example 1 of the present invention is that the polydopamine and hydrophilic polymer layers are not composited, so that the polyethylene microfiber membrane has no oil-water separation rate; the difference between Example 1 and Comparative Example 2 of the present invention is that the hydrophilic polymer PDMAPS layer is not composited, so that the oil-water separation efficiency of the polyethylene microfiber Janus composite membrane is unstable. Therefore, by modifying the polyethylene microfibers with a diameter of 500nm-20μm and a pore size of 1-50μm on one side through the polydopamine hydrophilic coating and PDMAPS layer assembled by self-polymerization of dopamine, the hydrophilicity and surface energy can be improved, giving the other side of the Janus composite membrane excellent hydrophilic properties. At the same time, the prepared polyethylene microfiber Janus composite membrane has a simple preparation process, good hydrophilic and hydrophobic double-sided anisotropy and excellent oil-water separation efficiency.
[0096] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0097] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it should be understood by those skilled in the art that the technical solutions recorded in the aforementioned embodiments can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present invention.
Claims
1. A polyethylene microfiber Janus composite membrane, characterized in that: It comprises a polyethylene microfiber membrane and a composite layer formed by the reaction of polydopamine and a hydrophilic polymer covering one side of the polyethylene microfiber membrane; The polyethylene microfiber membrane is prepared by an instantaneous pressure release method, and has a fiber diameter of 500nm-20μm and a pore size of 1-50μm; The hydrophilic polymer has a disulfide bond or a trisulfide bond group at the end; The polymer is one of poly-[2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide, polyethylene glycol, poly(N,N-dimethylacrylamide), polyvinyl pyrrolidone and polyacrylic acid.
2. The polyethylene microfiber Janus composite membrane according to claim 1, characterized in that: The disulfide bond group is one of a dithioester group, a xanthate group, and a dithiocarbamate group; And / or, the trisulfide bond group is a trithiocarbonate group.
3. A method for preparing the polyethylene microfiber Janus composite membrane according to claim 1, characterized in that: The method comprises: The polyethylene microfiber membrane is immersed on one side in a buffer solution containing dopamine to react, thereby obtaining a polydopamine@polyethylene microfiber membrane; The polydopamine@polyethylene microfiber membrane containing polydopamine is immersed in a mixed solution containing sodium borohydride and a hydrophilic polymer for reaction to obtain a polyethylene microfiber Janus composite membrane.
4. The method for preparing the polyethylene microfiber Janus composite membrane according to claim 3, characterized in that: The buffer solution includes tris(hydroxymethyl)aminomethane buffer with a concentration of 10-50 mM and a pH of 8.0-9.
0.
5. The method for preparing the polyethylene microfiber Janus composite membrane according to claim 3, characterized in that: The concentration of the buffer solution containing dopamine is 2-4 mg / mL.
6. The method for preparing the polyethylene microfiber Janus composite membrane according to claim 3, characterized in that: The polyethylene microfiber membrane is immersed on one side in the buffer solution containing dopamine for a reaction time of 12-36 hours.
7. The method for preparing the polyethylene microfiber Janus composite membrane according to claim 3, characterized in that: The concentration of the hydrophilic polymer is 2-4 mg / mL.
8. The method for preparing the polyethylene microfiber Janus composite membrane according to claim 3, characterized in that: The molar ratio of the hydrophilic polymer to sodium borohydride is 1:1-5.
9. The method for preparing the polyethylene microfiber Janus composite membrane according to claim 3, characterized in that: The polydopamine@polyethylene microfiber membrane containing polydopamine is immersed in a mixed solution containing sodium borohydride and a hydrophilic polymer for a reaction time of 12-36 hours.
10. A polyethylene microfiber Janus composite membrane prepared by the method for preparing the polyethylene microfiber Janus composite membrane according to any one of claims 3 to 9 and applied in the field of oil-water separation.
Citation Information
Patent Citations
Janus type micro-nano composite fiber membrane with super-hydrophobic single surface and super-hydrophilic single surface and preparation method of Janus type micro-nano composite fiber membrane
CN115418795A
